Analisis Stress Kerja Dan Displin Kerja Terhadap Efektivitas Sumber Daya Manusia (Studi Kasus Balai Pemuda dan Olahraga DIY) - Tri Isnandar, Irvan; Destiningsih, Rian (Jurnal Bisnisman : Riset Bisnis dan Manajemen, 2021)
Balai Pemuda dan Olahraga Daerah Istimewa Yogyakarta (BPO DIY) wants its employees to be able to work productively, with professional human resource management. A factor that is able to increase employee productivity, namely the effectiveness of human resources This research aims to be able to know the existence of stress and work discipline because if there is minimal stress and great discipline, it can increase the effectiveness of human resources in a job, especially in BPO DIY . The study was conducted by using descriptive analysis to be able to know the existence of work stress and work discipline on employees at BPO DIY. For processing the questionnaire data in this study using a validity and reliability test model. The conclusion of this study is that there is a relationship between work stress and work discipline with the effectiveness of human resources related to each other to improve the quality of work in (BPO DIY).